Prevalência de carcinomas espinocelulares de boca diagnosticados no laboratório de anatomopatologia bucal da Unifal - MG no período de 1998 a 2019 - Mamani, Laura Cruz (2021)
Squamous cell carcinoma (SCC) is the most common oral malignant tumor, representing 95% of all oral cancers. It is frequent in adult male patients, localized on lower lip, tongue and floor of mouth. The aim of this study was to evaluate the prevalence of oral SCC at Laboratory of Oral Anatomy and Pathology of Federal University of Alfenas (UNIFAL-MG) comparing clinical and demographical characteristics of the patients with microscopical aspects of the neoplasia, based on histopathological malignancy grade evaluation. The other objective was to analyze the evolution of the Service of oral diagnosis (reports) along its 22 years of existence. It was developed a retrospective study of all oral malignant neoplasias diagnosed from 1998 to 2019, collecting demographical data from the records of all biopsies received by the Service. OSCC classification was based on El-Naggar et al. (2017) criteria and histopathological grade of malignancy criteria was the one proposed by Anneroth; Batsalis; Luna (1987) and modified by Bryne et al. (1989). A total of 270 patients was evaluated; the lesions were frequently observed in men (71.5%), Caucasian (61.5%), age varied between 24 and 94 years (mean age 59.7 years), and were more localized on floor of mouth and lateral board of the tongue. The most frequent clinical aspect observed was infiltrative ulcer. SCC was the most frequent diagnosis and occurred in 145 patients (41.9%). Microscopically most tumors showed high grade of keratinization, pleomorfism Grade 2, pattern of invasion in thick cords and intense peritumoral inflammatory infiltration. The predominant score of tumors ranged from 5 to 10 (72.2%). Moreover, along the years there was a significant increase in the number of SCC diagnosed cases and an expansion of the coverage area of our Service.